Method of property organization and socialist state - Alexander V. Butakov (Правоприменение)
The subject. The article is devoted to the study of the relationship between property and the state-building in socialist States.The purpose of the article is to confirm or disprove the hypothesis that the socialist practice of state-building, depending on the combination of interaction of the main ways of organizing property, has a different social nature of existence. Methodology. The work provides the author’s methodology for studying the structure of the state, depending on the combination of interaction of the main ways of organizing property. The main results of the research. There are some possible basic options for the existence of a socialist practice of state building. After the disappointing results of the Soviet experience, the quite logical question is: what will be the future of the socialist concept of state-building and does it even exist? Socialist practice of state-building, depending on the combination of the interaction of the main ways of organizing property, has a different social nature of existence. The Soviet model was based on the liquidation of the private way of organizing property and the monopoly dominance of the forms of the general (collective) way of organizing it. The Chinese model, in which the monopoly of the forms of the general (collective) way of organizing property, corresponds to the legislative assumption of a private way of organizing it. The European Social Democratic model, where the private way of organizing property as the main system-forming one, acts in combination with forms of general (collective) and mixed (corporate) ways of organizing it.If we take into account that each method of organizing property is determined by the need to perform a specific social function, then in each model of socialist construction, depending on the particular combination of methods of organizing property, it is clear which of the social functions is dominant in the practice of construction. For example, if the main system-forming way of property organization is private, then this is a function of social development; if general (collective), then the function of social security, and finally, if mixed (corporate), then the function of social compromise (convergence). Such determination, in our opinion, is sustainable. Conclusions. Socialist practice of state-building has a different social nature of existence. This nature can be described provisionally as the Soviet, the Chinese and the European Social Democratic models.